PERKEMBANGAN HOTEL SYARI’AH DI INDONESIA; MENGONSEP PARIWISATA ISLAMI - Fahruddin Ali Sabri (Institut Agama Islam Negeri Madura)
Fahruddin Ali Sabri (Penulis, dosen STAIN Pamekasan, Jl. Raya Panglegur Km. 04 Pamekasan. Kontak 08521346464, e-mail didin021@yahoo.com) Abstract Indonesian tourism sector has been developed rapidly and significantly. Hotels sector high income contribution indicates the significant development, so it influences public prosperity. Syari’ah Hotel is one of the hotel models offering certain facilities that matches Islamic values. Its development opens promising market chance that must be grounded on non-alcohol, drug-abused free and adultery prohibition concept. It facilitates the guests to have comfortable and safe stay. Kata-kata kunci Hotel, Pariwisata dan Syarî’ah